The environmental dimension of sustainable development - Hamid, Noureddine (Journal of Economic, Administrative and Legal Sciences, 2019)
Since the Second World War, what has been called the development economics, which made the developed countries seek to achieve this development and at all levels economically, politically, socially and humanly, these countries sought to achieve all this and already reached what they wanted without taking into account this nature or the environment and what will happen? And what will happen to future generations? The concept of sustainable development emerged at the end of the last decade of the twentieth century. This concept was similar to the previous developmental concepts. It is concerned with satisfying the needs of the present and achieving social welfare, but not at the expense of future generations. Through the conservation of all natural resources, taking into account the environment that must be maintained and integrated into the policies of economic and social development from here emerged the importance of sustainable development, which takes into account the economy and Leah and the community.
Keywords: development economics; sustainable development; dimensions of sustainable development; environment